1 Route of admission in stemi: do patients who present directly to a PCI-capable hospital differ from inter-hospital transfers?. (9th June 2011) - Austin, D; Adam, Z; Shome, J; Awan, M; Sutton, A G C; Hall, J A; Wright, R A; Muir, D F; Swanson, N M; Carter, J; de Belder, MA
Abstract : Background: Rapid delivery of reperfusion therapy with PPCI is the gold standard treatment in STEMI. Systems have been developed, such as direct admission to a PCI-capable hospital, to minimise the time from diagnosis to PPCI. Despite this, a significant minority of patients are initially admitted to non-PCI capable hospitals. The aim of this study was to determine whether patients differed in their characteristics, time to PPCI, and outcome by route of admission. Methods: The study was performed in a single tertiary centre in North England. Data are collected routinely on all patients undergoing PPCI and include demographic, clinical and procedural variables. In-hospital MACCE (death, re-infarction or CVA) and mortality are collected providing relevant outcome measures. Baseline clinical variables by route of admission were compared and unadjusted in-hospital MACCE rates determined. One-year mortality by route of admission was calculated using the K-M product limit estimate. In-hospital and 1-year outcomes were analysed after adjustment for factors known to be predictors of early mortality following STEMI (models 1 and 3). To determine the relative importance of delays in treatment, call-to-balloon time was added (models 2 and 4). Logistic regression was used for the adjusted in-hospital outcomes, and Cox-proportional regression for adjusted 1-year mortality. Results: 2268 patients were included in the analysis. 510 patients (22.5%) were treated with PPCI following transfer from a non-PCI capable centre. Analysis of baseline variables (Abstract 1 table 1 ) showed the transfer group were more likely to have an LAD occlusion treated, and previous MI. Despite shorter DTB times, the transfer group had a greater median CTB time (52 minutes longer) compared with direct admissions. Other baseline variables were statistically no different between groups. There were 110 in-hospital MACCE events, and 168 deaths within 1-year follow-up. The transfer group had significantly higher unadjusted in-hospital MACCE rates (2.4% absolute, 58% relative increase (Abstract 1 table 2 )). At 1 year, the transfer group had significantly higher unadjusted mortality (2.7% absolute, 48% relative increase (Abstract 1 table 2 )). After adjustment for relevant co-variates (models 1 and 3) route of admission remained a significant predictor of in-hospital and 1-year mortality. With the addition of call-to-balloon time, no significant difference in outcome was noted by route of admission for either in-hospital or 1-year events. Conclusion: In this study, patients who presented directly had superior in-hospital and 1-year outcomes compared with those who required transfer from other hospitals. Adjustment for longer call-to-balloon times attenuated the finding of poorer outcomes in these patients, suggesting that delays in treatment are critical. Systems of care should be designed to avoid admission of STEMI patients to non-PCI hospitals, and facilitate more rapid transfer of patients where this has not been possible.